Case report: A rare low-grade fumarate hydratase-deficient renal cell carcinoma - Sun, Di; Hu, Baohong; Li, Xinna; Yang, Ping; Yu, Guohua (Frontiers in Oncology, 2024)
AimTo study and analyze the clinicopathological features of low-grade fumarate hydratase-deficient renal cell carcinoma in order to improve the understanding of the diagnosis and management of rare and specific morphological cases of this tumor.MethodsA case of low-grade FH-deficient renal cell carcinoma in a male is reported, and its clinicopathological features were analyzed and literature review was performed.ResultsA 48-year-old middle-aged male with no relevant positive clinical signs was admitted to the hospital with an incidental finding of a mass in the lower pole of the left kidney during abdominal CT examination. Pathomorphology showed that the tumor cells were arranged in a variety of structures and the cells were low grade eosinophilic. Immunohistochemistry showed Pax-8 (+), Vim (partially +), FH (-), CK7 (-), CD117 (-), P504s (partially +), CD10 (partially +), CA-9 (-), TFE3 (partially +), SDHB (+), CK20 (-), and Ki-67 (+, about 2%). Final pathologic diagnosis: FH-deficient renal cell carcinoma (low grade).ConclusionSingle pure low-grade FH-deficient renal cell carcinoma of the kidney is extremely rare, and the image structure of this tumor exhibits diverse manifestations, which needs to be differentiated from many renal tumors in clinicopathological diagnosis in order to prevent misdiagnosis.